Income Equality, School Performance and Educational Mobility - Philipp C. Bauer; Christoph A. Schaltegger (Center for Research in Economics, Management and the Arts (CREMA), 2011)
Is income equality a precondition for higher school performance and higher educational mobility? Or is the opposite true? We test empirically whether school performance and intergenerational transmission of educational attainment is depending on income equality on the local level. Using Swiss data, we take advantage of an exogenous variation across 2740 local municipalities. Our results point to a beneficial effect of income inequality on school performance for children with middle educated parents. In contrast, children with poorly educated parents as well as children with highly educated parents perform worse in more unequal communities. However, the popular idea that societies with a more equal income distribution inevitably enhance the upward mobility of disadvantaged children cannot be confirmed.
Keywords: I2; I21; I30; J24; D30; D31; D63; 330; inequality; intergenerational transmission; mobility; educational attainment; income distribution; human capital